3D printing of chitosan/ poly(vinyl alcohol) hydrogel containing synthesized hydroxyapatite scaffolds for hard-tissue engineering. (October 2019) - Ergul, Necdet Mekki; Unal, Semra; Kartal, Ilyas; Kalkandelen, Cevriye; Ekren, Nazmi; Kilic, Osman; Chi-Chang, Lin; Gunduz, Oguzhan
Abstract: In recent years, 3D printed scaffolds becoming a widespread tool, which supports the repair mechanism of natural tissues. In order to support this knowledge, we used 3D printing methods to fabricated Chitosan (CH)/poly(vinyl alcohol)(PVA)-based scaffolds contains with a various ratio of hydroxyapatite (HA) (2.5, 5, 10, and 15 wt%). These composited scaffolds were further characterized for their chemical, morphological, mechanical, and biocompatibility properties. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), swelling test, and compressive strength test were performed to reveal structural, mechanical and chemical characteristics of scaffolds. Among others, 15 wt% HA contained group demonstrated significantly superior and beneficial features in printing quality. Also, the results reveal that scaffolds have similar elastic modulus to natural bone. Bone morphogenetic protein-2 (BMP-2) protein was added to the most successful mechanically produced sample. As a result, it was shown that Chitosan/PVA/HA (15 wt%) with BMP-2 tissue scaffold could form a three-dimensional natural extracellular scaffold suitable for human mesenchymal stem cells. Altogether, these results show that hydroxyapatite added scaffolds produced may be a promising approach for bone tissue engineering applications. Highlights: FTIR results showed that hydroxyapatite was successfully sintered at 600 °C and particles size were at about 55.54 μm. The 36 layer of 15 wt.% of hydroxyapatite/Chitosan/PVA scaffolds were also successfully printed by a 3D printing. Due to this structure, the elastic modulus of the scaffold was determined at 91.14 MPa. 3D printed of CH/PVA/HA(15 wt.%) and CH/PVA/HA(15 wt.%)/BMP-2 scaffolds showed good biocompatibility, enhanced the attachment and proliferation of MSCs.